The isolated compounds from the twigs of Morus alba L. in Dong Thap - Nguyet, Bui Thi Minh; Khanh, Tran Huynh Nguyen (Vietnam Journal of Science and Technology, 2016)
From the ethyl acetate extract of the Morus alba L. (Moraceae) in Dong Thap, a triterpenoid, b-amyrin-b-D-glucopyranoside (1), a Diels – Alder type adducts, mulberrofuran G (2), a benzofuran, moracin M (3) and a prenylated flavonoid, kuwanon G (4) were isolated through repeated silica gel column chromatography. Their structures were identified by physicchemical and spectrometric methods.